Investigations on the abundance of ectoparasites and vector-borne pathogens in southwest Madagascar - Ehlers, Julian (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2020)
Human encroachment on natural habitats is steadily increasing due to the rapid growth of the worldwide population. The consequent expansion of agricultural land and livestock husbandry, accompanied by spreading of commensal animals, create new interspecific contact zones that are major regions of risk of the emergence of diseases and their transmission between livestock, humans and wildlife. Among the emerging diseases of the recent years those that originate from wildlife reservoirs are of outstanding importance. Many vector-borne diseases are still underrecognized causes of fever throughout the world and tend to be treated as undifferentiated illnesses. The lack of human and animal health facilities, common in rural areas, bears the risk that vector-borne infections remain unseen, especially if they are not among the most common. Ectoparasites represent an important route for disease transmission besides direct contact to infected individuals. While factors driving disease emergence are clearly visible in Madagascar, the knowledge of ectoparasites and potential pathogens is alarmingly limited. Following the One Health concept, this dissertation approaches the presence of ectoparasites and vector-borne bacteria, taking environmental factors and host ecology into account in order to identify possible transmission paths at the human/animal interface. The study took place in the northern portion of Tsimanampetsotsa National Park and the adjacent coastal strip in southwest Madagascar, in the dry and in the rainy season of 2016/2017. For the survey on ectoparasites species and the influence of habitat alteration, endemic mammals were trapped in transects of box traps installed in three habitats revealing different degrees of disturbance: Forest of the national park, degraded forest, and cultivated land. Additionally, Rattus rattus and Mus musculus were trapped inside villages, and livestock was sampled. I identified 17 species of ectoparasites, thirteen of which (blood-feeding lice, fleas and ticks) were subjected ...